Population change and the settlement system transformation in Poland, as revealed by the 2021 census - Vasilii L. Martynov; Irina Ye. Sazonova (Baltic Region, 2023)
This article aims to analyse current geodemographic changes in Poland, based on the data of the 2021 National Population and Housing Census. Methods, traditional for socioeconomic geography, such as zoning, were employed. Poland’s population decreased during the inter-census period (2011—2021), with the urban population declining faster than its rural counterpart. The large voivodeships aligned along the Vistula ‘axis’ — Mazowiecka, Lesser Poland and Pomerania — outperform other Polish regions in geodemographic terms. The situation is relatively favourable in Greater Poland, where the country’s main motorways converge. Districts and voivodeships where the geodemographic situation is more vulnerable can be divided into two groups: depressed and backward. The first one includes the traditionally industrial voivodeships of Southern and Central Poland; the second mainly consists of eastern voivodeships. The population decline in Eastern Poland is gathering pace: the 2021 census shows, a more or less favourable geodemographic situation is observed only in the main eastern cities and their environs. This state of affairs is largely due to the Polish government deliberately halting cooperation with Russia and Belarus, including cross-border collaborations. Yet, this decision seems to create more problems for Poland than its eastern neighbours. If the current trends persist, the eastern voivodeships, the stronghold of the right-wing conservatives in power, may not only rapidly lose population but also face a reduction in the level of socioeconomic development.